A Qualitative Evaluation of Training for Diverse Background PCAs in Aged Care - Yvonne Wells; Simon Haines; Phillipa Jane Mackey; Kane Solly; Ilsa Hampton (SAGE Publishing, 2024)
Most direct residential aged care is provided by personal care assistants (PCAs), with western societies increasingly relying on culturally diverse aged care workers. In Australia and internationally, studies have reported that the level of training in both instrumental and relational care for PCAs is insufficient and inconsistent. This study evaluated the impact of The Little Things training program, designed for culturally diverse PCAs and students training to become PCAs. A modified Most Significant Change process, comprising a group-based qualitative analysis of narratives, was used to gain a rich understanding of the impacts and outcomes of the training. Narratives supplied by 29 PCAs and students were reviewed with aged care and training organization managers, who identified six themes: Increased confidence; Taking time; Building rapport and collaboration; Awareness of new skills; Seeing the whole person; and Positive impact on the resident. These themes reflected two key aims of The Little Things training: improving PCAs' communication with residents and increasing PCAs' confidence in communicating with residents. The study findings showed that The Little Things training program can improve the confidence of PCAs to communicate with aged care residents and may improve their capacity to form relationships.